1981
DOI: 10.1136/bjo.65.6.401
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of map-dot-fingerprint changes in the cornea.

Abstract: SUMMARY Map-dot-fingerprint basement-membrane abnormalities of the cornea are common in the geieral population, affecting as many as 76 % of persons over age 50 and 42% of persons of all ages. The prevalence of this condition in the general population is not significantly different from that found in families of patients with recurrent corneal erosions and map-dot-fingerprint corneal changes. Despite this extremely high prevalence of basement-membrane changes the incidence of recurrent erosive symptoms in tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Another possibility is that aberrant basement membrane with poor adhesion properties may develop in some cases, yet appear morphologically normal by IVCM. The complexity of the clinical-morphological relationship is underscored by our observation of severe, grade 3 EBMD morphology in unoperated, asymptomatic eyes of patients in this study, echoing earlier observations reported by Labbé et al 19 Given the prevalence of EBMD in the general population 1,3 and given the findings in this study, the clinical-morphological correlations in EBMD appear to be complex. Further studies are required at the morphological, ultrastructural, biochemical, and genetic levels to gain a deeper understanding of EBMD, its treatment and the ultimate clinical implications.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Another possibility is that aberrant basement membrane with poor adhesion properties may develop in some cases, yet appear morphologically normal by IVCM. The complexity of the clinical-morphological relationship is underscored by our observation of severe, grade 3 EBMD morphology in unoperated, asymptomatic eyes of patients in this study, echoing earlier observations reported by Labbé et al 19 Given the prevalence of EBMD in the general population 1,3 and given the findings in this study, the clinical-morphological correlations in EBMD appear to be complex. Further studies are required at the morphological, ultrastructural, biochemical, and genetic levels to gain a deeper understanding of EBMD, its treatment and the ultimate clinical implications.…”
Section: Discussionsupporting
confidence: 87%
“…[1][2][3] While most cases of EBMD are asymptomatic, in about 10%, symptoms of painful recurrent corneal erosions (RCE) or degraded vision are present 1 and require clinical attention. A number of these patients, however, are unresponsive to conservative treatment measures (such as lubricant ointments and therapeutic contact lenses) and are considered for surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence varies between 2% and 42% in the general population. 17,18 Intraepithelial lesions that resemble geographic map-like gray patches, dots, or microcysts and fingerprint or whorl-like patterns characterize this dystrophy. No known systemic associations are described.…”
mentioning
confidence: 99%
“…The anatomical nature of the causing pathology allows in many cases treatment. This is especially true for strictly epithelial alterations such a s microcysts and corneal dystrophies (Germundsson et al, 2010) [5] which are rather common (Werblin et al 1981) [6].…”
Section: Discussionmentioning
confidence: 99%